Determination of surge arrester discharge energy using finite element analysis method. Issue 6 (1st September 2015) - Illias, Hazlee Azil; Abd Halim, Syahirah; Abu Bakar, Ab Halim; Mokhlis, Hazlie
Abstract : Surge arrester is widely used as a protective device to reduce possibility of flashover during transient overvoltage event. The device needs to withstand high energy discharged by the overvoltage which may increase the degradation rate of its characteristics. In this study, a set of transmission line surge arresters with different dimensions and ratings was simulated to investigate their discharge energy capabilities during fast‐front surge events using the finite element analysis method. To validate the accuracy of the method, the arrester models were also simulated by the use of PSCAD/EMTDC and EMTP‐RV software and compared with the specifications provided by the manufacturer. In spite of distinctive representations of the arrester models in COMSOL Multiphysics, EMTP‐RV and PSCAD, the comparison made between the simulation results indicates a satisfactory agreement. The manufacturers' data were used to validate that the proposed simulation model is acceptable. It was found that the simulation results were comparable with the manufacturer's test data of the discharge voltages and energy withstand capability, thus proving that all studied cases were adequately modelled. Parametric analyses were also conducted using finite element method to study the effects of varying the design geometry of the ZnO blocks and the arrester's housing on the energy absorption, which cannot be evaluated using PSCAD and EMTP‐RV software.